Catalytic Generation of Radicals from Nitroalkanes - Kashihara, Myuto; Kosaka, Kohei; Matsushita, Naoki; Notsu, Shunta; Osawa, Ayumi; Nakao, Yoshiaki (Synlett, 2022)
A new protocol for the catalytic denitrative generation of radicals from nitroalkanes was disclosed. 9-Fluorenol acts as a single-electron transfer catalyst that reduces nitroalkanes to promote the C-NO2 bond cleavage, followed by the formation of alkyl radicals. The obtained radicals participate in diverse transformations such as hydrogenation, Giese addition, spirocyclization, and Minisci reactions by using appropriate trapping reagents. The present system outperforms conventional methods using tin hydrides in terms of cost, toxicity, and experimental operations.
Keywords: nitroalkane; 9-fluorenol; single-electron transfer; denitration; radical; organocatalysis